2014
DOI: 10.2319/100813-743.1
|View full text |Cite
|
Sign up to set email alerts
|

Canine retraction and anchorage loss: Self-ligating versus conventional brackets in a randomized split-mouth study

Abstract: Objective: To evaluate the velocity of canine retraction, anchorage loss and changes on canine and first molar inclinations using self-ligating and conventional brackets. Materials and Methods: Twenty-five adults with Class I malocclusion and a treatment plan involving extractions of four first premolars were selected for this randomized split-mouth control trial. Patients had either conventional or self-ligating brackets bonded to maxillary canines randomly. Retraction was accomplished using 100-g nickel-tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
0
27
0
4
Order By: Relevance
“…The application of lower forces with SLB did not influence the anchorage control. Even though there are three reports [19][20][21] comparing loss of anchorage of molars when retracting teeth with SLB or CB, no reports have compared the loss of anchorage between SLB and CB when retracting lower canines. Those three reports, although measuring anchorage loss in different arches, agree with our findings that no difference exists between bracket types.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The application of lower forces with SLB did not influence the anchorage control. Even though there are three reports [19][20][21] comparing loss of anchorage of molars when retracting teeth with SLB or CB, no reports have compared the loss of anchorage between SLB and CB when retracting lower canines. Those three reports, although measuring anchorage loss in different arches, agree with our findings that no difference exists between bracket types.…”
Section: Discussionmentioning
confidence: 94%
“…Even though Electronic supplementary material The online version of this article (doi:10.1007/s00784-016-1855-7) contains supplementary material, which is available to authorized users. some reports have ruled out the superiority of one bracket type over another when the retraction of maxillary canines are compared [12,14,19], it could be argued that the rates for mandibular canines might be different if they tend to rotate more than the upper canines do due to different positions of their axes of resistance. Up to this point, only one report [14] compared SLB and CB, and the results suggest that there is no effect of bracket type while retracting lower canines.…”
Section: Introductionmentioning
confidence: 96%
“…Scott et al 22 showed no difference in efficiency of initial alignment in a randomized controlled trial between patients with self-ligating brackets versus conventional brackets. Similarly, da Costa Monini et al 23 found no difference in rate of canine retraction between conventional and self-ligating appliances in a splitmouth design experiment.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The animals were fasted for 12-hours and then sedated with an intramuscular injection of ketamine (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) mg/kg IM) mixed with xylazine (0.22 mg/kg IM). Dental prophylaxis using an ultrasonic scaler irrigated with 0.12% chlorhexidine gluconate was performed and bone markers [6 mm long Imtec miniscrew implants (3M Unitek, Monrovia, CA)] were placed for radiographic reference.…”
Section: Pre-surgical Preparationmentioning
confidence: 99%
“…Ante esta debilidad metodológica se desarrollaron estudios de boca dividida, (en la hemiarcada superior e inferior de un solo lado se colocaron un tipo de brackets mientras que en la otra hemiarcada se colocó otro tipo de bracket), estos estudios tienen mayor control de los factores ambientales. (12)(13)(14)(15)(16)(17) El estudio hecho por el Dr. André da Costa Moninia por el método de "boca dividida" hace la comparación auto-ligados vs convencionales en la retracción de caninos, para lo que se realizó evaluaciones radiográficas antes y después de completarse la retracción, la superposición de los cefalogramas permitió encontrar que los caninos superiores presentaron similares tiempo de retracción con ambos tipos de brackets en la arcada superior, encontrando similares resultados en la perdida de anclaje, así como en los cambios de la inclinación de caninos y molares superiores. (12) Estudios que evalúan la velocidad de retracción del canino, deslizando el diente a lo largo de un arco de alambre, establecen que este tiende a ser más rápido con brackets convencionales que con los de auto-ligado.…”
Section: Revista Evidencias En Odontología Clínicaunclassified